Pembawaan Dan Keturunan Sebagai Faktor Pembentuk Kepribadian Anak - Hutagalung, Maria Berdika Agustina; Simatupang, Roselly (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Innate and hereditary are important things in a person who will later lead that person to be ready to enter the environment. The world recognizes that this is not the only determining factor in the formation of a child's personality in society. As one of the important factors that need to be considered. How are children genetically born from certain families, and then these children are included in a family environment that also contributes from different sides. Parents are the first environment in which they will contribute to the child. Innate and heredity is something that cannot be discarded in a child. Thus, in the future, children are shaped by many other factors, however, in this research, the focus lies in how capable parents and practitioners of spiritual education are to encourage children to maximize what they have and to be assisted by what is provided by the environment in shaping the child's personality. . As a practitioner of Christian religious education, it has become our main duty to lead these children to become individuals according to God's will in His word.Keywords: heredity, personality, children